The influence of the Tiflis entourage on the formation of Mykhailo Hrushevsky's personality - Romantsova , Natalya (Skhid, 2023)
The proposed study analyzes issues related to the formation of M. Hrushevsky's personality in Tiflis (Tbilisi) - the cultural center of the South Caucasus, where he spent his youth, studying in a gymnasium. The peculiarities of this region were considered and it was clarified how the entourage of Tiflis influenced the personality of young Mykhaylo. This, in the opinion of the article’s author, is important for a full understanding on the historical significance of the figure of Hrushevsky. In particular, the author draws attention to the influence of the Tiflis entourage in the matter of establishing the personality markers of young Mykhailo – the beginning of his intellectual biography formation, the way of establishing his Ukrainian patriotism, interests in Ukrainian studies, history of Ukraine, literature, folklore. Analysis of M. Hrushevsky's life gymnasium period permits to reveal the combination of creativity, innovation, unusual efficiency, ambition, and perseverance in his activities. Theoretical studies of authoritative foreign and Ukrainian scientists F. Brodel, L. Kjell, D. Ziegler, Ya. Vermenych, P. R. Magochy, S. Maksymenko and others are included in the analysis of the chosen subject. According to the interdisciplinary approach, the article combines elements of regional history, social psychology, and sociology.